The impact of polyvinylpyrrolidone on properties of cadmium oxide semiconductor nanoparticles manufactured by heat treatment technique - Al-Hada, Naif Mohammed; Saion, Elias; Talib, Zainal Abidin; Shaari, Abdul Halim (MDPI, 2016)
Cadmium oxide semiconductor nanoparticles were produced using a water based mixture, incorporating cadmium nitrates, polyvinyl pyrrolidone (PVP), and calcination temperature. An X-ray diffraction (XRD) evaluation was conducted to determine the degree of crystallization of the semiconductor nanoparticles. In addition, scanning electron microscopy (SEM) was conducted to identify the morphological features of the nanoparticles. The typical particle sizes and particle dispersal were analyzed via the use of transmission electron microscopy (TEM). The findings provided further support for the XRD outcomes. To determine the composition phase, Fourier transform infrared spectroscopy (FT-IR) was conducted, as it indicated the existence of not only metal oxide ionic band in the selection of samples, but also the efficient removal of organic compounds following calcinations. The optical characteristics were demonstrated, so as to analyze the energy band gap via the use of a UV–Vis spectrophotometer. A reduced particle size resulted in diminution of the intensity of photoluminescence, was demonstrated by PL spectra. Plus, the magnetic characteristics were examined using an electron spin resonance (ESR) spectroscopy, which affirmed the existence of unpaired electrons.